Teachers, Schools, and Society: Resource for Exploring Education (Cases, Readings, and Observations) - Myra Pollack Sadker (McGraw Hill Higher Education, 2005)
File dalam bentuk PDF, Word, Audio dan Video (Quicktime), dll; Isi: Acrobat Reader, LA, Media (Media, Xtras, Sadker), Quicktime Installer, Xtras, Autorun, dll; Judul Dalam Kemasan.